2020
DOI: 10.2337/db20-37-or
|View full text |Cite
|
Sign up to set email alerts
|

37-OR: Racial and Socioeconomic Disparities in the Use of Newer Classes of Diabetes Medications

Abstract: Among patients with type 2 diabetes (T2D), racial/ethnic minorities and those of lower socioeconomic status (SES) have a higher burden of coronary artery disease, chronic kidney disease, and hypoglycemia. Therefore, these groups may especially benefit from newer diabetes medication classes (GLP-1 receptor agonists, DPP-4 inhibitors, SGLT2 inhibitors), but high cost may limit access. We conducted a secondary analysis of the Look AHEAD (Action for Health in Diabetes) randomized trial to assess the associations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“… 67 This is also supported by a recent secondary analyses of the Look-AHEAD (Action for Health in Diabetes) trial, showing racial and social-economic status disparities in the use of innovative glucose lowering medications (ie, DPP-4i, or SGLT-2i or GLP-1RAs). 68 Beyond the analyses of pattern of GLP-1RAs use by race/ethnic group, there is a lack of data on RWS evaluating the effectiveness of GLP-1RAs in these populations, underlining therefore the need for further RCTs and RWS on this aspect.…”
Section: Effectiveness Vs Efficacymentioning
confidence: 99%
“… 67 This is also supported by a recent secondary analyses of the Look-AHEAD (Action for Health in Diabetes) trial, showing racial and social-economic status disparities in the use of innovative glucose lowering medications (ie, DPP-4i, or SGLT-2i or GLP-1RAs). 68 Beyond the analyses of pattern of GLP-1RAs use by race/ethnic group, there is a lack of data on RWS evaluating the effectiveness of GLP-1RAs in these populations, underlining therefore the need for further RCTs and RWS on this aspect.…”
Section: Effectiveness Vs Efficacymentioning
confidence: 99%
“…Therefore, the pharmacist comanaged group does not include confounding factors of different family medicine providers. While the Look AHEAD study included DPP‐4 inhibitors, these agents were not included in this study because these agents have not been shown to have the cardiovascular benefit or renal protective features of GLP‐1 agonists and SGLT‐2 inhibitors 6 . They also are considered more weight neutral than other medication classes and are not emphasized by the guidelines for common comorbidities 2 .…”
Section: Discussionmentioning
confidence: 99%
“…They also are considered more weight neutral than other medication classes and are not emphasized by the guidelines for common comorbidities 2 . Therefore, it was decided to not include these agents, despite their inclusion in the secondary analysis of the Look AHEAD trial 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations